The Effect Of Online Customer Experience, Product Quality, and Service Quality On SMEs Customer Loyalty - Fajar Adi Prakoso; Najmudin Najmudin; Weni Novandari; Nandang Bekti Karnowati; Devy Widya Apriandi (Profesional Muda Cendekia Publishing, 2023)
This study aimed to ascertain the impact of online customer experience, product quality, and service quality on customer loyalty in SMEs. This study was conducted In Tangerang Selatan, Indonesia. A purposive sample technique was employed to acquire data. There were 150 responders in this survey. The SmartPLS 3.3 software tool performed partial least squares (PLS)-based structural equation modeling (SEM). According to the study, online customer experience and product quality substantially impact consumer loyalty. In contrast, service quality has no impact on consumer loyalty. The most important factor affecting customer loyalty is product quality which needs attention. If the product is of high quality, customers will be satisfied and will tend to buy again and recommend the business to others who can help increase the number of customers.